Hepatocellular Senescence: Immunosurveillance and Future Senescence-Induced Therapy in Hepatocellular Carcinoma - Liu, Peng; Tang, Qinghe; Chen, Miaomiao; Chen, Wenjian; Lu, Yanli; Liu, Zhongmin; He, Zhiying (Frontiers in Oncology, 2020)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths worldwide. The lack of effective targeted drugs has become a challenge on treating HCC patients. Cellular senescence is closely linked to the occurrence, development, and therapy of tumor. Induction of cellular senescence and further activation of immune surveillance provides a new strategy to develop HCC targeted drugs, that is, senescence-induced therapy for HCC. Precancerous hepatocytes or HCC cells can be induced into senescent cells, subsequently producing senescence-associated secretory phenotype (SASP) factors. SASP factors recruit and activate various types of immune cells, including T cells, NK cells, macrophages, and their subtypes, which carry out the role of immune surveillance and elimination of senescent cells, ultimately preventing the occurrence of HCC or inhibiting the progression of HCC. Specific interventions in several checkpoints of senescence-mediated therapy will make positive contributions to suppress tumorigenesis and progression of HCC, for instance, by applying small molecular compounds to induce cellular senescence or selecting cytokines/chemokines to activate immunosurveillance, supplementing adoptive immunocytes to remove senescent cells, and screening chemical drugs to induce apoptosis of senescent cells or accelerate clearance of senescent cells. These interventional checkpoints become potential chemotherapeutic targets in senescence-induced therapy for HCC. In this review, we focus on the frontiers of senescence-induced therapy and discuss senescent characteristics of hepatocytes during hepatocarcinogenesis as well as the roles and mechanisms of senescent cell induction and clearance, and cellular senescence-related immunosurveillance during the formation and progression of HCC.